Un japonisme patrimonial - Damien Delille (In Situ)
Behind fashion heritage from Japan there is a complex history associated with the vogue for Japanism that France witnessed during the second half of the nineteenth century. This article sets out to analyse the different stages in the history of how Japanese textile objects and items of clothing integrated private and public collections, looking at the actors involved in this process, merchants, collectors, artists and scientists. The notion of a clothing and textile heritage in Japan is examined, in the context of the westernisation of the country during the Meija era, between 1868 and 1912. The study of the part played by universal exhibitions, in particular the Vienna exhibition of 1873, leads to the identification of the earliest collections of fukusa, kimonos and other elements of Japanese dress, creations dating from before the opening up of Japan to western influences. At the beginning of the twentieth century, the Paris Musée des Arts décoratifs and the Lyons Textile Museum both acquired several of these collections, aiming to make the special practices they witnessed available to the general public and textile industries. The article explores this long process which allowed for non-western items of clothing to enter heritage history in France and Japan.